Dampak Revolusi Industri 4.0 Terhadap Struktur Pekerjaan dan Keterampilan Tenaga Kerja di Sumatera Utara - Simamora, Jesika Melina; Januardani, Fandra Dikhi; Sipayung, Rosintan (DAS Institute, 2025)
This study aims to determine the impact of the industrial revolution 4.0 on the job structure and skills of the workforce in North Sumatra. In this study, the approach used is a qualitative method. The results of the research obtained to overcome the challenges of unemployment and skills gaps, retraining and reeducation are very important solutions. Training programs designed to upskill the workforce should be structured with the current and future needs of the industry in mind. For example, governments and educational institutions can work together to develop training programs that focus on digital skills, programming, and data analysis, which are urgently needed in the era of the Industrial Revolution 4.0. Several companies in North Sumatra have started implementing internal training programs to improve the skills of their employees. For example, a manufacturing company in Medan has launched a competency-based training program that aims to improve the technical and managerial skills of employees. The program not only helps employees to adapt to new technologies, but also improves the company's overall productivity and efficiency.